Inflation Forecasting in Indonesia Using Lee’s Fuzzy Time Series Method - Sari, Virgania (Universitas Negeri Semarang, 2025)
Inflation is an important economic indicator, the rate of growth is should be low and stable. Unstable inflation will complicate people's decisions to consume, invest and produce which in turn will reduce economic growth. One of the effects of this inflation is slow economic growth. For this reason, the government needs to consider policies that can influence it. Bank Indonesia one of the policies to control inflation is monetary. Forecasting methods are used to help facilitate future planning and can be used as guidelines for decision making that can improve economic performance. Forecasting used is fuzzy time series Lee. The data used is monthly inflation data in Indonesia for the period January 2017-May 2022. The error rate used is MAPE which produces a very good MAPE value of 8,16%. Forecasting results for the next period, June 2022, amounted to 3,66%.